Model Peningkatan Minat Belajar Melalui Penerapan Strategi Index Card Match Kombinasi Student Teams-Achievement Divisions Dalam Pembelajaran Pendidikan Kewarganegaraan Pada Siswa Kelas Viii-G SMP Negeri 1 Wonosari Klaten Tahun Pelajaran 2015/2016 - YOGA PRATAMA, RIZKY, Dra. Sundari, SH., M.Hum (2016)
This study aims to improve the learning interest in learning Civic Education at class VIII-G SMP Negeri 1 Wonosari Klaten academic year 2015/2016 through the implementation of strategies Index Card Match combinations of Student Teams-Achievement Divisions. Students who have a high interest in learning prior to testing models only 5 children (15.6%) of the 32 participants learners. Master has sought to overcome these problems but the results have not been optimal. The solution offered in this research is through the implementation of strategies Index Card Match combinations Student Teams-Achievement Divisions. Subjects in this study are students of class VIII-G SMP Negeri 1 Wonosari Klaten academic year 2015/2016, amounting to 32 learners. The research data were collected through an informant, places, and events on going learning activities. Data collection techniques by using questionnaires, interviews, observation and documentation. The procedures in this study consists of five stages: problem identification, problem solution planning, test planning models, models of implementation of testing, and refinement of the product. The results of this study indicate that interest in learning at class VIII-G SMP Negeri 1 Wonosari Klaten academic year 2015/2016 after testing the model by applying a combination of strategies Index Card Match Student Teams-Achievement Divisions increased to 25 children (78.1%).